Revisão Sistemática da Literatura sobre Abordagens para Adaptação de Processos Baseadas em BPMN - Pillat, Raquel M.; Santos, Renata M. S.; Oliveira, Toacy C. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2019: Anais do XV Simpósio Brasileiro de Sistemas de Informação, 2019)
Business Process Model and Notation (BPMN) is an OMG and ISO standard for business process modeling and a standard in professional practice. However, business processes are not static and often need to be tailored to specific contexts where they will be applied or improved as a result of new business requirements. In such contexts, adaptations are performed to produce new variant processes that meet new needs. Ideally, adaptations should be managed in some way in order to prevent organizations from having repositories containing numerous variant models for the same business process without any relationship established between them. Since the BPMN standard does not provide any adaptation support for processes specified with the language, the objective of this paper was to investigate which approaches/techniques have already been proposed in the literature to manage design-time adaptations of process models in BPMN. We have conducted a systematic literature review that resulted in 11 selected works. This review showed that design-time variations on BPMN processes are managed through variability modelling (6 works) or flexible changes (5 works); there are few process adaptation approaches specifically designed for the BPMN language; and such approaches are still quite immature.